Is agroforestry likely to reduce deforestation? - Angelsen, A.; Kaimowitz, D. (Island Press, 2004)
Is agroforestry likely to reduce deforestation? Most agroforesters for the past 15 years have said "yes", some adding "by about 5 ha of reduced deforestation per ha of agroforestry adopted". The authors argue, nevertheless, that in many cases the answer is likely to be either "it depends" or even "no". The aim with this chapter is to discuss key factors which condition the agroforestry - deforestation link. That is, what makes a "yes" more likely than a "no"?. The reformulated question therefore is: which types of agroforestry under what conditions are likely to reduce the conversion of natural forest?. This chapter provides a systematic review of arguments for and against agroforestry as a means to reduce deforestation.